Direct Estimation for Approximation by Bernstein Polynomial by Using Ditzian-Totik and Average in L Ja,h11 p < oo Modulus of Smoothness - Kasim, N. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The purpose of the paper is to tind the degree of the approximation of a functions f be bounded , measurable and defined in interval [a,h]by Bernstein polynomial in LP space 1 p < oo by using Ditzian-Totik modulus of smootlmess and k 1n average modvlus of smoothness.